Efficacy of repeated low-level red-light therapy combined with defocus incorporated multiple segments spectacles for controlling childhood myopia - Chang-Kang Luo; Chun-Yan Lai; Jia-Hao Tan; Wei Zhao; Qing-Qing Tan (Photodiagnosis and Photodynamic Therapy)
Objective: To evaluate the differences in the efficacy of repeated low-level red-light (RLRL) therapy combined with either single-vision spectacles (SVS) or defocus incorporated multiple segments (DIMS) spectacles in slowing myopia progression in children. Methods: A total of 129 myopic children aged 6–14 years were recruited between July 2023 and February 2024. Participants had at least one eye with spherical equivalent refraction (SER) <-0.50D and astigmatism ≤ 3.00D after cycloplegia. They were divided into four groups: SVS, DIMS, RLRL combined with SVS (RCS), and RLRL combined with DIMS (RCD). The RCS and RCD groups wore spectacles and received daily RLRL therapy sessions. The primary outcome was the change in axial length (AL) at 12 months. Results: After 12 months, the mean changes of AL were: 0.26 mm (95 % CI, 0.17 to 0.35 mm) for SVS, 0.16 mm (95 % CI, 0.11 to 0.21 mm) for DIMS, -0.21 mm (95 % CI, -0.45 to 0.02 mm) for RCS, and -0.14 mm (95 % CI, -0.27 to -0.01 mm) for RCD. Significant differences were observed between groups (F = 15.18, P < 0.001). Post-hoc tests showed that the RCS and RCD groups exhibited significantly greater shortening compared to the SVS and DIMS groups (all P < 0.001). However, no significant difference was observed between the RCS and RCD groups (P > 0.05). No severe adverse events or safety concerns related to RLRL therapy were observed throughout the study. Conclusion: RLRL therapy is a potentially effective and practical approach for myopia control, demonstrating comparable efficacy when combined with either SVS or DIMS spectacles.